Storehouse housing architectural elements of Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
This is the on-site storehouse housing several architectural elements and sculptural fragments found in Neelkanth Mahadev Temple and the entire temple complex. These fragments are important to understand the original fabric of the temple structure.